2010
DOI: 10.3102/0013189x10390804
|View full text |Cite
|
Sign up to set email alerts
|

Attribution Error and the Quest for Teacher Quality

Abstract: Social psychologists are persuaded that researchers as well as laymen tend to overestimate the influence of personal traits and underestimate the influence of situations on observed behavior. The author of this article suggests that education researchers and policy makers may be overestimating the role of personal qualities in their quest to understand teaching quality. In their effort to understand classroomto-classroom differences in student learning, they may focus too much on the characteristics of teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
174
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(187 citation statements)
references
References 36 publications
5
174
0
8
Order By: Relevance
“…We concur with the statements of Kershner et al (2013) and Kennedy (2010) that school organisation and culture can indeed act to constrain teachers' professional learning and certainly in the case of our study, many of those teachers whose leaders were not involved voiced reasons why they felt their actions at school were constrained. On the contrary, the teachers in this study whose leaders co-participated found that there was a positive school-wide culture and they felt supported to experiment with new ideas and practices.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We concur with the statements of Kershner et al (2013) and Kennedy (2010) that school organisation and culture can indeed act to constrain teachers' professional learning and certainly in the case of our study, many of those teachers whose leaders were not involved voiced reasons why they felt their actions at school were constrained. On the contrary, the teachers in this study whose leaders co-participated found that there was a positive school-wide culture and they felt supported to experiment with new ideas and practices.…”
Section: Discussionsupporting
confidence: 65%
“…Kennedy (2010) pointed to the need to understand the situational factors that impact on teachers' practices. According to Clarke and Hollingsworth (2002), since growth can occur through a variety of networks, professional development should be designed so that participants can enact change in many ways and through varied change sequences.…”
Section: Literature Teacher Changementioning
confidence: 99%
“…Kennedy d identified numerous external factors that contribute to an altered perception of teacher quality such as the shape of the room, allotted time for teaching, availability of classroom materials, and additiona l work assignments beyond teaching. Additionally, contextual constraints such as lack of preparation time, participation in other non-related teaching activities, students' absenteeism, and selection of inappropriate curriculum materials for instruction can reduce the perceived quality of a teacher (Kennedy, 2010). Therefore, the certification process in countries such as the United States, in which teachers reflect on their instructional practices and then have chances to adjust their thinking during their portfolio development process is influenced by these contextual factors (Sato, Wei, & Darling Hammond, 2008).…”
Section: Defining Teacher Qualitymentioning
confidence: 99%
“…In sum, teacher quality is the resource necessary for teaching that teachers bring to the classrooms. Kennedy (2010) admitted that the measurement of teacher quality could be based on characteristics such as experience and test scores but argued about the underestimation of adjustments that need to be made for situational factors when considering the quality of teachers. Kennedy d identified numerous external factors that contribute to an altered perception of teacher quality such as the shape of the room, allotted time for teaching, availability of classroom materials, and additiona l work assignments beyond teaching.…”
Section: Defining Teacher Qualitymentioning
confidence: 99%
“…Researchers of teacher knowledge (Brown, 2002(Brown, , 2009Kennedy, 2010;Charalambous et al, 2012) posit that teachers' use of curriculum materials is influenced by their knowledge; and by looking into the two resources (curriculum materials and teacher knowledge) in tandem with other contextual factors, it throws light on understanding how teachers can be prepared and equipped with the knowledge to perceive and mobilize curriculum materials effectively.…”
Section: Teacher Knowledge and Its Relevance To Use Of Curriculum Matmentioning
confidence: 99%